A new species of the genus Sulcohumpacris Yin, Yin et Cao, 2017 (Orthoptera, Acridoidea, Pamphagidae) from China - Li, Xin-Jiang; Zhi, Yong-Chao; Yin, Zhan (Zootaxa, 2020)
A new species of the genus Sulcohumpacris Yin, Yin et Cao, 2017 i.e. Sulcohumpacris wuanensis sp. nov. is described in this paper from China. The new species is similar to Sulcohumpacris hebeiensis Yin, Yin et Cao, 2017 but differs from latter by median keel of pronotum cut by hind sulcus slightly, tegmen of male cover 2/3 tympanum, length of Krauss’ organ 1.8 times of width in female, apex of subgenital plate of male point, cercus of male narrow at base, lower margin of Epiphallus with large projection in the middle and hind knee of female not curved at lower margin. Type specimens are deposited in the College of Life Sciences, Hebei University, Baoding, China.